Doing cultural theory - Walton, David (Sage Publications, 2012)
A textbook-toolkit that teaches students the basics of cultural theory by unpacking its complexities with real-life examples and student focused pedagogy. Goes beyond showing how others have analysed and interpreted the world to demonstrate to students how to do cultural theory themselves